Chronic tracheostomy care of ventilator‐dependent and ‐independent children: Clinical practice patterns of pediatric respirologists in a publicly funded (Canadian) healthcare system. Issue 1 (11th October 2022) - St‐Laurent, Aaron; Zielinski, David; Qazi, Adam; AlAwadi, Aceel; Almajed, Athari; Adamko, Darryl J.; Alabdoulsalam, Tareq; Chiang, Jackie; Derynck, Michael; Gerdung, Chris; Kam, Karen; Katz, Sherri L.; et al.
Abstract: Objectives: To describe the current clinical practice patterns of Canadian pediatric respirologists at pediatric tertiary care institutions regarding chronic tracheostomy tube care and management of home invasive ventilation. Methods: A pediatric respirologist/pediatrician with expertise in tracheostomy tube care and home ventilation was identified at each Canadian pediatric tertiary care center to complete a 59‐item survey of multiple choice and short answer questions. Domains assessed included tracheostomy tube care, caregiver competency and home monitoring, speaking valves, medical management of tracheostomy complications, decannulation, and long‐term follow‐up. Results: The response rate was 100% (17/17) with all Canadian tertiary care pediatric centers represented and heterogeneity of practice was observed in all domains assessed. For example, though most centers employ Bivona™ (17/17) and Shiley™ (15/17) tracheostomy tubes, variability was observed around tube change, re‐use, and cleaning practices. Most centers require two trained caregivers (14/17) and recommend 24/7 eyes on care and oxygen saturation monitoring. Discharge with an emergency tracheostomy kit was universal (17/17). Considerable heterogeneity was observed in the timing and use of speaking valves and speech‐language assessment. Inhaled anti‐pseudomonal antibiotics are employed by most centers (16/17) though the indication, agent, and protocol varied by center. Though decannulation practices varied considerably, the requirement of upper airway patency was universally required to proceed with decannulation (17/17) independent of ongoing ventilatory support requirements. Conclusion: Considerable variability in pediatric tracheostomy tube care practice exists across Canada. These results will serve as a starting point to standardize and evaluate tracheostomy tube care nationally.